Factors Associated with Discontinuing Exclusive Breastfeeding among Mothers of Infants Aged 0-6 Months - Dhakal, Binita; Thapa, Pratima (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Knowing breastfeeding is one of the easiest and cost-effective ways to maintain a good child health, majority infants are not exclusively breastfed for the recommended 6 months of age. Thus, the aim of the study was to find out the factors associated with discontinuing exclusive breastfeeding (EBF) among mothers of infants’ aged 0-6 months. Methods A analytical study design was used to find out the factors associated with discontinuing EBF among mothers of infants’ aged 0-6 months in Nepal. A total of 380 mothers of infants whose child were 0-6 months old were selected using non-probability purposive sampling technique through online survey as people are advised to stay at home during the Covid-19 outbreak. Data was collected using structured questionnaire with interview technique. Results Study findings revealed that half (50.5%) of the mothers exclusive breastfed their infants with mother’s mean age being 27.39 ± 3.64 years. Discontinuation of EBF varied with mothers age, ethnicity, mother’s educational level, initiation of breastfeeding and sources of information regarding EBF as newspaper/articles and relatives/friends/neighbors (p=<0.005). The factors related to mother that are associated with discontinuation of EBF were found to be perceived insufficient milk, cesarean section delivery, jobholder mother (p= <0.001) respectively. Conclusions Only half of respondents exclusively breastfed their infants for the recommended age in which only factors related to mother were significant with discontinuation of EBF rather than infants’. Findings of the study emphasizes on counselling the mothers regarding the benefits of EBF to both child and mother during hospital visits. Keywords: exclusive breastfeeding; factors; under 6 months; EBF.